Effects of Combined Milrinone and Levosimendan Treatment on Systolic and Diastolic Function During Postischemic Myocardial Dysfunction in a Porcine Model. (September 2016) - Axelsson, Birger; Häggmark, Sören; Svenmarker, Staffan; Johansson, Göran; Gupta, Anil; Tydén, Hans; Wouters, Patrick; Haney, Michael
It is not known whether there are positive or negative interactions on ventricular function when a calcium-sensitizing inotrope is added to a phosphodiesterase inhibitor in the clinical setting of acute left ventricular (LV) dysfunction. We hypothesized that when levosimendan is added to milrinone treatment, there will be synergetic inotropic and lusitropic effects. This was tested in an anesthetized porcine postischemic global LV injury model, where ventricular pressures and volumes (conductance volumetry) were measured. A global ischemic injury was induced by repetitive left main stem coronary artery occlusions. Load-independent indices of LV function were assessed before and after ventricular injury, after milrinone treatment, and finally after addition of levosimendan to the milrinone treatment. Nonparametric, within-group comparisons were made. The protocol was completed in 12 pigs, 7 of which received the inotrope treatment and 5 of which served as controls. Milrinone led to positive lusitropic effects seen by improvement in tau after myocardial stunning. The addition of levosimendan to milrinone further increased lusitropic state. The latter effect could however not be attributed solely to levosimendan, since lusitropic state also improved spontaneously in time-matched controls at the same rate during the corresponding period. When levosimendan was added to milrinone infusion, there was no increase in systolic function (preload recruitable stroke work) compared to milrinone treatment alone. We conclude that in this model of postischemic LV dysfunction, there appears to be no clear improvement in systolic or diastolic function after addition of levosimendan to established milrinone treatment but also no negative effects of levosimendan in this context.